Triage in disasters: A conceptual analysis - Setyawati, Asih Dewi; Lu, Yu-Ying (Jurnal Keperawatan Padjadjaran, 2025)
Background: Disaster triage faces significant challenges due to definitional conflicts and ambiguities. Conducting a concept analysis of disaster triage is essential for clarifying its meaning, improving decision-making, ensuring effective training, and enhancing disaster preparedness for healthcare professionals. Thus, this study aims to define the concept of disaster triage and identify its attributes, antecedents, and consequences using Walker and Avant's framework. Method: The methodology involved a comprehensive literature review from 2013 to 2024, focusing on nurse-related triage during emergencies and disasters. Articles were gathered from databases such as Web of Science, PubMed, Scopus, Cochrane Library, and Google Scholar. After screening the titles, abstracts, and full texts, 30 articles met the inclusion criteria. Result: Following Walker and Avant's framework, the concept analysis revealed that disaster triage is influenced by various antecedents, attributes, and consequences. Antecedents such as education, working experience, and disaster training provide the foundation for effective triage practices, while attributes such as clinical judgment, assessment skills, and effective communication are crucial in the triage process itself. The consequences of effective disaster triage include enhanced patient safety and care delivery efficiency. Conclusion: In conclusion, this study provides valuable insights that deepen the understanding of the concept of disaster triage and also provides valuable guidance for clinical practice and informs future research in the fields of disaster management and emergency nursing.